PROCEDIMENTO ESTATÍSTICO PARA VALIDAÇÃO DE ANALISTAS EM ENSAIOS MICROBIOLÓGICOS QUANTITATIVOS - TAKADA, Veruska Norie; OLIVEIRA, Anderson Castro Soares de; PASCOA, Marcelino Alves Rosa de; MARTINS, Marcelo Aparecido (Brazilian Journal of Biometrics, 2018)
Food microbiology laboratories perform various types of tests to detect and quantify the presence of microorganisms. However these tests are subject to interference and imperfections. Thus, laboratories should establish a quality control program to ensure quality of practices carried out in the laboratory. In this context, the objective of this paper is establish a statistical protocol for validation of analysts as part of a quality control system for quantitative microbiological analysis. Thus, simulations of analyst validation were performed considering a completely randomized design and subsequent analysis of the data by means of ANOVA and ANDEV tests. The results show that ANDEV is better at detecting the variability among analysts and presented a lower rate of type I error, more power with a smaller number of repetitions, adapting better to the routine and the reality of laboratories.